Receding horizon output feedback control for linear systems with input saturation - Lee, Y; Kouvaritakis, B; SOCIETY, ICS; SOCIETY, ICS; SOCIETY, ICS (2000)
In this paper, a constrained receding horizon output feedback control method which is based on a state observer is suggested. The proposed method adopts the receding horizon dual-mode paradigm which consists of a 'feasible invariant set' and 'free control moves'. Polyhedral feasible invariant sets of estimated state are derived along with guaranteed bounds on state estimation errors. The guaranteed bounds on the state estimation error are developed by considering invariant sets of state estimation errors which include possible initial estimation errors. Predictions of future states are made based on estimated current state and bounds on current estimation error. The free control moves are determined so that the predicted future state belongs to the polyhedral feasible invariant set, despite input constraints and measurement noise.